Reform of the System of Education in Pesantren - Erniati, Erniati (Hunafa: Jurnal Studia Islamika, 2017)
Impact of pesantren education system update can be viewed in terms of its negative and positive aspects. The negative side, schools that still persists in the form of salafiless able to again growConduciveand schools that have been developed into a boarding Khalafihave started to tend to the economic orientation that has implications for the values of sincerityless. While the positive impact schools have the ability to survivein the midst of change and competition continues to run, has the ability to improve its quality, and has the ability to evolve and adapt to the ever-changing era guidance. The challenges facing the education system reform schools, namely the challenge of macro and micro. At the macro level schools are challenged to work on institutional Triumvirate, namely the family, workplace, and schools themselves. While the micro, schools are required to rearrange the interaction between students and Kiai, the concept of education, and the curriculum used.